2011
DOI: 10.1590/s0100-879x2011007500015
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations and placental immunostaining of interleukin-10 and tumornecrosis factor-α as predictors of alterations in the embryo-fetal organism and the placental development of diabetic rats

Abstract: 0.05). Prevalence analysis showed that the IL-10 expression followed TNF-α expression, showing a balance between them. STZ rats also presented impaired reproductive performance and reduced plasma IL-10 levels related to damage during early embryonic development. However, the increased placental IL-10 as a compensatory mechanism for the deficit of maternal regulation permitted embryo development. Therefore, the data suggest that IL-10 can be used as a predictor of changes in the embryo-fetal organism and in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
(16 reference statements)
3
9
1
2
Order By: Relevance
“…Increased plasma levels of TNF-α have been reported by other groups in experimental diabetes in mice and rats (Lukic et al 1998; Jain et al 2007) and in human type 1 diabetics (Padgett et al 2013). Plasma IL-10 levels has been reported to fall in STZ rats (Sinzato et al 2011) but an increase in plasma IL-6 (Jain et al 2007) or IFN-γ levels (Lukic et al 1998) reported previously in STZ-treated rats were not measured in the present study. Although plasma cytokine values may be important because they translate to human studies, there are relatively few studies and results may vary according to the animal model used.…”
Section: Discussioncontrasting
confidence: 69%
“…Increased plasma levels of TNF-α have been reported by other groups in experimental diabetes in mice and rats (Lukic et al 1998; Jain et al 2007) and in human type 1 diabetics (Padgett et al 2013). Plasma IL-10 levels has been reported to fall in STZ rats (Sinzato et al 2011) but an increase in plasma IL-6 (Jain et al 2007) or IFN-γ levels (Lukic et al 1998) reported previously in STZ-treated rats were not measured in the present study. Although plasma cytokine values may be important because they translate to human studies, there are relatively few studies and results may vary according to the animal model used.…”
Section: Discussioncontrasting
confidence: 69%
“…This alteration would explain the implantation loss observed in our previous experiments (Barão et al, 2008b;Dorce et al, 2014). Moreover, our results agree with Sinzato et al (2011), who observed that diabetic rats had decreased IL-10 and an increase in pre-and post-implantation losses. Given their crucial role in the brain development, it is not surprising that elevated levels of proinflammatory cytokines generated by the maternal or fetal immune system have been associated with abnormal fetal brain development and increased risk for neurodevelopmental disorders and are responsible for many apparently unexplained behavioral effects occurring in adulthood (Meyer et al, 2009).…”
supporting
confidence: 92%
“…This method was first demonstrated in 1974 by Portha et al to the neonatal rats by applying 100 mg/kg STZ (62). Dağıstanlı et al (63) have used STZ in the 100 mg/kg concentration through i.p while Sinzato et al (64) have used STZ in the same concentration, but through sc This method has been the mostly preferred chemical diabetes mellitus model to create type II diabetes because it offers operational ease. Similarly, it is considered to be the best model to reflect type II diabetes mellitus clinic among the other models (40) .…”
Section: Animal Models Of Diabetes Mellitusmentioning
confidence: 99%